2023
DOI: 10.1029/2022ja031002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Southern Hemisphere Mid‐High Latitude Thermospheric ∑O/N2 Responses to the Space‐X Storm

Abstract: The response of thermosphere composition to geomagnetic storms has been explored for several decades since the pioneering work by Seaton (1956). Based on the observations from satellite-borne gas analyzers and numerical modeling, Prölss (1980Prölss ( , 1981 and Burns et al. (1991) summarized how the thermospheric composition responds to geomagnetic storms. When a storm begins, enhanced Joule heating produces neutral temperature gradients in the polar region. Consequently, a composition disturbance is generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 78 publications
(127 reference statements)
1
21
0
Order By: Relevance
“…The SH condition is similar to Cai et al. (2023), who argued that the dominant positive B y in the SH (Feb, summer hemisphere) led to the occurrence of ΣO/N 2 depletion in the local morning. The equatorward winds are generated in the local morning due to ion‐neutral coupling (Zhang et al., 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The SH condition is similar to Cai et al. (2023), who argued that the dominant positive B y in the SH (Feb, summer hemisphere) led to the occurrence of ΣO/N 2 depletion in the local morning. The equatorward winds are generated in the local morning due to ion‐neutral coupling (Zhang et al., 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, different ∑O/N 2 responses in the two hemispheres during geomagnetic storms can be anticipated. However, most of the previous studies using GOLD ∑O/N 2 focused on the one hemisphere response (Cai et al, 2020(Cai et al, , 2021a(Cai et al, , 2021b(Cai et al, , 2022(Cai et al, , 2023Yu et al, 2022aYu et al, , 2022b to geomagnetic disturbances. The studies using GOLD observed ∑O/N 2 in both hemispheres are all related to the ∑O/N 2 response to lower atmospheric driving (Krier et al, 2021;Oberheide et al, 2020) and seasonal variations (Qian et al, 2022).…”
mentioning
confidence: 99%
“…The GOLD mission has been making synoptic disk observations of daytime thermospheric composition and temperature since late 2018. The studies using the GOLD data include temperature changes during various geomagnetic activities (Laskar et al., 2021); composition changes during a solar eclipse (Aryal et al., 2020), nighttime ionospheric structures (Eastes et al., 2023; Karan et al., 2020), and geomagnetic storms (Cai et al., 2020, 2021, 2023; Correira et al., 2021; Gan et al., 2020a; Karan et al., 2023). Lower and upper atmosphere coupling via atmospheric waves has also been observed by the GOLD mission (Gan et al., 2020b; Gan, Qian, et al., 2023; Gan, Oberheide, et al., 2023; Krier et al., 2021; Oberheide et al., 2020, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The ratios of height‐integrated number density of atomic oxygen (O) to that of molecular nitrogen (N 2 ), namely column O/column N 2 density ratio (∑O/N 2 ), which can be deduced by disk‐viewing optical observations of OI 135.6 nm and Lyman‐Birge‐Hopfield radiances (Meier, 2021; Strickland et al., 1995), has been widely utilized to describe thermospheric neutral composition responses to geomagnetic storms and the storm effects on ionospheric plasma density (e.g., Cai et al., 2020, 2021a, 2021b, 2023; Crowley et al., 2006; Eastes et al., 2020; Lee et al., 2013; Liou et al., 2005; Strickland et al., 1999, 2001; Wang et al., 2021; Yu et al., 2022a, 2022b; Zhai et al., 2023; Zhang et al., 2004). Previous studies demonstrated the evolution and physical processes of ∑O/N 2 during geomagnetic storms, which is briefly summarized as follows.…”
Section: Introductionmentioning
confidence: 99%